Analysis of the Effect of Ergonomics on Increasing Work Productivity in Welding Operators at PT. TRSS uses Rapid Body Entire Assessment (REBA) Method - Isma Wahyu Yunian; Sartono; Abu Naim; Nirfison; Adelia Dwi Valentin; Purwani Husodo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The welding process on the AM65511000 type radiator product at PT TRSS in the Curug area is a heavy job that is still done manually. Improper posture and repeated acceptance of static loads for a long period can result in operator fatigue, thereby reducing productivity. The analysis was carried out using Pareto diagrams and fishbone diagrams. Ergonomics analysis with the REBA method is one method to evaluate the overall posture and work attitude of workers. In this study, an analysis of the REBA method was carried out on workers in the welding process section on the AM65511000 type radiator product to determine the risks faced by workers and the improvements that could be proposed. The research was conducted referring to the REBA worksheet by Hignett and McAtamney. From the studies that have been carried out, it was found that workers have a moderate risk with a value of 5 which means that an immediate investigation and implementation is needed in the form of changes in work posture or work environment. The highest risk value was obtained in assessing the bent body posture when moving the radiator. Suggestions that can be made include lowering the level of the holder, optimizing the position of the torso and weight point, and making a table that can be adjusted in height and tilted angle.